The Balance of Legal Protection Between the Rights of Patients and Medical Personnel from the Perspective of Health Law - Dilly Hermanto; Jumiati Jumiati; Alifiya Rofikhatul Ula; Hernawati Hernawati (Civiliza Publishing, 2026)
This study aims to analyze the balance of legal protection between the rights of patients and medical personnel from the perspective of Law Number 17 of 2023 concerning Health. The dynamics of healthcare services demonstrate the need for fair legal certainty for patients as service recipients and for medical personnel as professional practitioners. This study uses normative legal methods with a statutory and conceptual approach. Legal materials are analyzed qualitatively through systematic and teleological interpretation of provisions governing patient rights, consent for medical procedures, and professional protection for medical personnel. The results show that normatively, the law has accommodated a balance of legal protection by strengthening patient rights and providing protection for medical personnel who work according to professional standards. However, challenges remain in the implementation aspect, particularly in dispute resolution mechanisms and proving medical negligence.